The Relationship Between Body Mass Index (BMI) and Pain Intensity in Patients With Lumbar Nucleus Pulposus Hernia (HNP) - Patria Adri Wibhawa; Tranggono Yudo Utomo; Agus Yudawijaya; Gabriella Natasha Levina Sihombing (CV. Inara, 2026)
Lumbar Herniated Nucleus Pulposus (HNP) is one of the main causes of low back pain that can reduce the quality of life of sufferers. Risk factor that affect the intensity of pain in HNP patients include body mass index (BMI). An increase in BMI can cause additional mechanical stress on the lumbar spine, alter posture, and exacerbate pain. The purpose of this study was to determine the relationship between BMI and pain intensity in patients with lumbar HNP at Budhi Asih General Hospital. This study used an analytical observational research method with a cross-sectional approach. The study sample consisted of 54 patients. BMI data obtained from measuring the patients' height and weight were classified according to WHO categories, while pain intensity was measured using the Visual Analog Scale (VAS) instrument. Data analysis using the Chi-Square test showed a significant relationship between BMI and pain intensity in patients with lumbar HNP (P < 0.029). These findings indicate that obesity increases the mechanical load on the lumbar spine, thereby exacerbating pain in HNP patients. In conclusion, there is a significant relationship between BMI and pain intensity in lumbar HNP patients. Therefore, weight control through a healthy lifestyle and appropriate rehabilitation programs is expected to reduce pain intensity and improve patients' quality of life.